Rare Earth Elements (REE) Extraction from The Stones Hill at Padang Area by Precipitation - Oknovia Susanti; Zeky Azizi (Postgraduate, University of Mataram, 2024)
Rare Earth Elements (REE) are a very important element in modern life such as electronics, materials engineering, and even medicine. Gadolinium (Gd) is one of the REEs that is used as a basic material for implants as well as being used for other basic materials such as a corrosion inhibitor, control rods for nuclear reactors, and others. In this case, the elements are found along hills in the Padang area which have the potential to be produced in large quantities from six rock minerals such as granite, basalt, clay, silica, tuff, and limestone.). Based on the results of identification using the XRF spectrometer test tool, it was found that the six mineral rocks had an abundance of rare earth elements. The results of testing the extraction of Gadolinium Oxide (Gd2O3) using XRF were successfully carried out, Gd2O3 can be extracted by 0.06% - 1.84% in basalt rock, 0.47% - 0.95% in clay rock, and 0% - 0.88% in silica rock. This proves that the main rock minerals from stones have the Rare Earth Elements (REE) and can be extracted with using the Precipitation Extraction method.